Ganoderma Spore Lipids Inhibit Perineural Invasion in Pancreatic Cancer by Downregulating NGF-TrkA Pathway - Haohui Lin MS; Manhon Chung MD; Yi Yang MS; Li Zhang MS; Xiaohua Pan MD; Sa Cai MD, PhD; Yu Pan PhD (Journal of Evidence-Based Integrative Medicine)
Perineural invasion (PNI) is an important factor leading to the recurrence of pancreatic cancer (PanCa). The NGF–TrkA pathway is related to PNI progression. Ganoderma spore lipid (GSL) is a drug with anti-cancer properties. In this study, we find out whether GSL can prevent PNI of PanCa by inhibiting NGF–TrkA pathway. In vitro , wound healing assays, transwell-based assays and three-dimensional tumor-nerve cell co-culture system showed that GSL significantly inhibited the migration and invasion capacity of PanCa cells. Inhibiting the NGF–TrkA pathway is considered an effective approach for treating PanCa. We showed that GSL effectively inhibited NGF-TrkA pathway via immunofluorescence assays and western blotting analysis. The supplement of recombinant NGF reversed the GSL inhibitory effect on the migration and invasion of PANC-1. In vivo , a sciatic nerve invasion animal model was constructed using BALB/c mice. GSL significantly suppressed tumor growth and suppressed the expression of TrkA, NGF, and vimentin and upregulated the level of the epithelial marker E-Cadherin. Moreover, GSL reduced the expression of S100 and PGP9.5. These findings suggested that GSL effectively inhibited the PNI of PanCa cells by downregulating the NGF–TrkA pathway, which may provide a new adjuvant for PanCa treatment.